THE INFLUENCE OF WATER ADDING ON THE OPTIMUM MOISTURE CONTENT OF 1 DAY CURING CLAY COMPACTION - Cassiophea, Lola (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2015)
The level of soil density measured from the value of the dry volume weight. Testing was conducted on the physical properties of soil and compaction test on one day curing. In the standard compaction test variation I (6%, 8%, 10%, 12%, 14%), it is obtained optimum moisture content of 24% and a maximum dry volume weight value of 1.335 t / m3. Testing compaction variations II (7%, 9%, 11%, 13%, 15%), it is obtained optimum moisture content of 26.5% and a maximum dry volume weight value of 1,270 t /m3. At compaction testing modifications variation I (6%, 8%, 10%, 12%, 14%), it is obtained optimum moisture content of 14.4% and a maximum dry volume weight value of 1,870 t /m3. Testing compaction variations II (7%, 9%, 11%, 13%, 15%), it is obtained optimum moisture content of 13,7% and a maximum dry volume weight value by 1,94 t /m3. In the second test, the value of optimum moisture content greater than the first test, while the maximum weight of the dry volume is smaller than the first test. This shows that the addition of the percentage variation in the use of water in the compaction test with one day curing showed that the optimum water content decreases while the maximum dry weight of volume showed increase.